A randomized controlled trial to examine the effects of the Tackling Teenage psychosexual training program for adolescents with autism spectrum disorder. (9th March 2017) - Visser, Kirsten; Greaves‐Lord, Kirstin; Tick, Nouchka T.; Verhulst, Frank C.; Maras, Athanasios; van der Vegt, Esther J.M.
Abstract : Background: Previous research underscores the importance of psychosexual guidance for adolescents with autism spectrum disorder (ASD). Such guidance is provided in the Tackling Teenage Training (TTT) program, in which adolescents with ASD receive psycho‐education and practice communicative skills regarding topics related to puberty, sexuality, and intimate relationships. This randomized controlled trial investigated the effects of the TTT program on (a) cognitive outcomes (i.e. psychosexual knowledge, and insight in interpersonal boundaries) and (b) behavioral outcomes (i.e. skills needed for romantic relationships and problematic sexual behavior). Methods: A total of 189 cognitively able adolescents with ASD, aged 12–18 years old, were randomized to an intervention condition ( n  = 95) or a waiting‐list control condition ( n  = 94). We assessed outcomes using self‐reported as well as parent‐reported questionnaires at baseline (T1), posttreatment (T2; after 6 months), and follow‐up (T3; after 12 months). Results: Linear mixed model analyses showed significant treatment effects for psychosexual knowledge and adequate insight in boundaries, both posttreatment and at follow‐up. All adolescents increased significantly over time in their social responsiveness and decreased their problematic sexual behavior, irrespectively of condition. The TTT program was most effective for younger adolescents with ASD; following the TTT program resulted in higher psychosexual knowledge, and higher social functioning for these adolescents. Conclusions: The results of this study indicate that the TTT program is effective as a psycho‐educational program to provide adolescents with ASD with the knowledge and insight they need to prepare themselves for a healthy psychosexual development. Further research is needed to investigate how this increased knowledge and insight can subsequently ameliorate improvements in romantic skills and prevent the development of problematic sexual behavior and victimization.